2011
DOI: 10.1016/s1470-2045(11)70044-4
|View full text |Cite|
|
Sign up to set email alerts
|

A 3′-untranslated region KRAS variant and triple-negative breast cancer: a case-control and genetic analysis

Abstract: Summary Background We previously identified a functional variant in a let-7 microRNA (miRNA) complementary site in the 3′-untranslated region of the KRAS oncogene (rs61764370) which is associated with cancer. We aimed to investigate the association of this KRAS variant with breast cancer and tumour biology. Methods We assessed frequency distributions of the KRAS variant in 415 patients with histologically confirmed breast cancer and 457 controls from Connecticut, USA (study group 1) and association of this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
115
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 119 publications
(121 citation statements)
references
References 33 publications
(47 reference statements)
6
115
0
Order By: Relevance
“…Furthermore, there is no significant difference in the frequency of the G-allele (TG/GG genotype) KRAS-LCS6 polymorphisms either across cancer groups or between cancer and general population reported in study by Chin LJ 1. Similarly, Paranjape 6 found no difference in the overall frequency distributions of the KRAS-variant genotype in cases of breast cancer and controls. In this study, a significant association of the KRAS-LCS6 was only found in a group with breast cancer in premenopausal patients with oestrogen/ progesterone-negative tumours.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Furthermore, there is no significant difference in the frequency of the G-allele (TG/GG genotype) KRAS-LCS6 polymorphisms either across cancer groups or between cancer and general population reported in study by Chin LJ 1. Similarly, Paranjape 6 found no difference in the overall frequency distributions of the KRAS-variant genotype in cases of breast cancer and controls. In this study, a significant association of the KRAS-LCS6 was only found in a group with breast cancer in premenopausal patients with oestrogen/ progesterone-negative tumours.…”
Section: Discussionmentioning
confidence: 92%
“…Germline SNP (rs61764370) has been recently extensively studied in relation to several types of cancer, especially in connection with associated risk, prognosis, and/or treatment response/resistance to therapy [1][2][3][4][5][6][7][8][9][10][11] . The let-7 family of miRNAs has been found to play an important role in tumorigenesis by regulating the expression of multiple oncogenes, including KRAS.…”
Section: Introductionmentioning
confidence: 99%
“…1 One of the first mutations discovered in this class is the KRAS-variant, a let-7 binding site mutation in the 3 0 UTR of the KRAS oncogene. 2 This mutation predicts an increased risk of several cancers, including non-small cell lung cancer, 2 triple negative breast cancer (TNBC) in premenopausal women 3 and ovarian cancer. [4][5][6] The KRAS-variant also predicts unique tumor biology, with tumors in KRAS-variant patients exhibiting a KRAS-addicted signature, as well as an estrogen negative, basal-like gene expression pattern.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6] The KRAS-variant also predicts unique tumor biology, with tumors in KRAS-variant patients exhibiting a KRAS-addicted signature, as well as an estrogen negative, basal-like gene expression pattern. 3,5 Perhaps most powerful is the extensive evidence that the KRAS-variant is biologically functional, as exemplified by its role as a strong biomarker of response to cancer therapy. KRAS-variant patients with ovarian cancer or head and neck cancer are cisplatin resistant, 5,7 those with colon cancer or head and neck cancer exhibit cetuximab sensitivity, 7,8 and those with non-small cell lung cancer (NSCLC) are resistant to erlotinib but sensitive to sorafenib.…”
Section: Introductionmentioning
confidence: 99%
“…5,6 In addition, miRNA disruptions through inherited variants in their binding sites or coding sequences are strong genetic markers of cancer risk. [7][8][9][10][11][12] One of the first such variants, located in the 3' untranslated region (3'UTR) of the KRAS oncogene and referred to as the KRAS-variant, has been associated with altered miRNA signatures in tumors 7 as well as poor outcome and response to treatment in several cancers (Ratner et al submitted), 13,14 while a variant in the KIT 3'UTR is associated with acral melanoma. 9 These findings suggest that miRNA 3'UTR-binding variants may be associated with melanoma and can also lead to miRNA expression alterations and altered biology in the tumors that they are associated with.…”
Section: Introductionmentioning
confidence: 99%